Agronomy undergraduate students’ perceptions of ethics and animal welfare in relation to animal-based entertainment - Valverde, Anthony (2024)
Introduction. Agronomy undergraduate students recognize the importance of animal production to satisfy the nutritional requirements of society; however, there is an epistemological gap regarding the use of animals in recreational activities. Objective. To explore the ethical and bioethical perceptions of students concerning animal welfare and the use of animals for entertainment purposes. Materials and methods. A survey was conducted among active students enrolled in the Agronomy Engineering program at the Instituto Tecnológico de Costa Rica (ITCR) during 2023, to evaluate their perceptions about animal welfare and the ethical use of animals in recreational activities. The application of the instrument allowed to describe the characteristics of the observed phenomenon in relation to the students’ perceptions of animal welfare. The data were analyzed using a t test to examine whether the means of two independent groups were significantly different from each other. Results. The level of concern for animal welfare in the student population was high (70.8 %, n = 102, p < 0.001). Furthermore, this concern was four times higher if the respondent was a woman compared to men (odds ratio 4.44, p < 0.001). The students indicated that there is a gradation of animal suffering (56.7 %, n = 81, p < 0.001), and the majority considered it to be unethical to perform entertainment activities using animals (73.6 %, n = 106, p < 0.05). Conclusion. The students expressed support for animal welfare and recognized the ethical responsibility of humans towards animals to avoid unnecessary suffering. It is suggested to incorporate multidisciplinary approaches in the curricula of Agronomy-adjacent degrees regarding human-animal relationship studies.